Monte Carlo simulation of ammonia adsorption in nanoporous carbon: Optimal pore sizes for adsorption refrigeration applications - Nasser D. Afify; Martin B. Sweatman (Adsorption Science & Technology)
Climate change and the continual rise in cooling demand means more efficient and environmentally friendly refrigeration technologies are required more than ever. One attractive route to reducing future demand is to improve adsorption refrigeration technologies based on natural refrigerants such as ammonia. The choice of ammonia adsorbent plays an important role in achieving improved refrigeration efficiency and suitable operating conditions. This paper reports a detailed study on the role of pore size on thermal efficiency, desorption temperature and cooling capacity of ammonia–carbon adsorption refrigeration systems. Systematic Monte Carlo simulations were conducted to study ammonia adsorption in carbon slit-pores with pores sizes ranging from 0.5 nm to 3.0 nm. Simulations were carried out at temperatures between 0°C and 50°C and pressures up to 15.0 bar. It is found that nanoporous carbon with very small pore sizes is not a good adsorbent for thermally efficient adsorption refrigeration systems. However, carbon mesopores can provide higher refrigeration capacities and coefficients of performance together with lower desorption temperatures, thus offering the possibility of relying on low-grade thermal waste heat to drive the refrigeration process.